Optimization of functional Multilayer and few layer Ti3C2 MXene Synthesis and their characterization as new generation of 2D material for cutting-edge development - Lotfi, RoyaL (International Journal of Psychosocial Rehabilitation, 2020)
MXene as a new family of 2D structures opens the window for preparing advanced materials which are applicable in different zones.MXenes can be achieved through chemical etching of MAX phases.Since Bonding energy of M-A in various MAX phases are differen, MXenepreaperation procedure should be optimized.Present work gives guidelines about various parameters should be considered to achieve high qualified MXenefrom MAX phases which was supplied from foresman company.Two procedures (using HF solution and Fluoride-based salt solution) were applied for Ti3AlC2 etching.Investigations proposed that for HF solution: concentration, temperature and contact time of 40%, room temperature and 60 h resulted in qualified products according to color change, XRD and FESEM analysis. In the second method using Fluoride-based salt, 50 ˚C and 60 h using 0.5 g TiR3RAlCR2R, 0.8 g LiF and 9 M HCl resulted in TiR3RCR2R flakes with desired characteristics.